2013
DOI: 10.1002/wrcr.20320
|View full text |Cite
|
Sign up to set email alerts
|

Investigating storage‐discharge relations in a lowland catchment using hydrograph fitting, recession analysis, and soil moisture data

Abstract: [1] The relation between storage and discharge is an essential characteristic of many rainfall-runoff models. The simple dynamical systems approach, in which a rainfall-runoff model is constructed from a single storage-discharge relation, has been successfully applied to humid catchments. Here we investigate (1) if and when the less humid lowland Hupsel Brook catchment also behaves like a simple dynamical system by hydrograph fitting, and (2) if system parameters can be inferred from streamflow recession rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 24 publications
4
47
1
Order By: Relevance
“…This result do not comply with that of Brauer et al (2013), who found that for a less-humid catchment in the Netherlands parameter calibration for a power-law storage-discharge relationship led to a strong underestimation of the response of runoff to rainfall while parameter estimation from recession analysis lead to an overestimation.…”
Section: Model Calibration and Validationcontrasting
confidence: 95%
See 2 more Smart Citations
“…This result do not comply with that of Brauer et al (2013), who found that for a less-humid catchment in the Netherlands parameter calibration for a power-law storage-discharge relationship led to a strong underestimation of the response of runoff to rainfall while parameter estimation from recession analysis lead to an overestimation.…”
Section: Model Calibration and Validationcontrasting
confidence: 95%
“…The differences may arise due to the difference between the polynomial relationship derived from the recession analysis in this study and the pre-determined power-law relationship in Brauer et al (2013), and the differences in the calibration and the runoff routing algorithms.…”
Section: Model Calibration and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Teuling et al (2010) also applied this approach to the Prealpine Rietholzbach catchment (3.31 km 2 ) getting good results in wet periods and poor model performance during dry periods. The study of Brauer et al (2013) showed similar results for the Dutch lowland Hupsel Brook catchment (6.5 km 2 ) where discharge results were correctly reproduced only in certain periods. Melsen et al (2014) determined the minimum amount of data required to find robust parameter values for a simple Kirchner (2009) model with two parameters in the Prealpine Rietholzbach catchment (3.31 km 2 ).…”
supporting
confidence: 59%
“…A single value of measured discharge is used to initialize the simulation. In addition, Kirchner (2009) Brauer et al (2013) used a parameter f that takes into account the difference between potential and actual evapotranspiration on a monthly basis.…”
Section: Discharge Simulationmentioning
confidence: 99%